The effect of changing the rules on score fluctuation and match duration in the FIVB women's beach volleyball - Giatsis, G. (International Journal of Performance Analysis in Sport, 2003)
The purpose of this study was to investigate the differences between the two scoring systems, Rally Scoring (RS) and Side Out scoring (SO), in the duration and the score fluctuation of matches in Federation Internationale de Volleyball (FIVB) Women's Beach Volleyball (BV). In this research the duration and the points of 1253 matches were recorded from 22 tournaments of the FIVB Women's BV World Tour. The 2000 FIVB tournaments followed the SO system and the 2001 FIVB followed the RS system. Since the 2001 FIVB was played in 2 winning sets, it was divided in two subgroups concerning the final score (RS2-0 and RS2-1). The 2000 FIVB was played in a single set of 15 points. The one way ANOVA indicated that there were significant differences (F(3,1835) = 268.091, p< .001) in total duration of matches between the tournaments. The Post Hoc Scheffe indicated significant differences between the SO (M = 35.5, SD = 9.9 min) and the RS (M = 41.6, SD = 10.2 min) and he SO and the RS2-1 (M = 53.8, SD = 7.2 min). In SO matches the losers won (M = 8.1, SD = 3.7 points), while in the RS mean match phases were (? = 83.5, SD = 17.4). 46.4% and 12.7% of the matches included a set with the minimum difference of points in the RS and SO respectively. In conclusion, RS increased match duration due to the third set and the matches were more wavering and spectacular as more sets finished with the minimum difference of points. However, the physical demands of the game were increased due to the greater number of rallies.